Upaya Mengurangi Kesepian Melalui Pengembangan Self-Compassion Pada Ibu Rumah Tangga di Pedesaan - Amalia Agustina Amalia; Nurul Hikmah; Marhamah (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2025)
Loneliness is an emotional condition that negatively impacts psychological well-being, particularly among housewives who often experience limited social interaction. This study aims to identify the causes of loneliness and explore the application of self-compassion as a strategy to alleviate it, focusing on housewives in Hakim Wih Ilang Village, Bandar District, Bener Meriah Regency. A descriptive qualitative approach was used, with data collection involving in-depth interviews and observations of seven key informants, all of whom are widows. The results show that loneliness among housewives is influenced by feelings of isolation, a lack of emotional closeness, minimal social support, and the burden of responsibilities. Self-compassion was applied through practices such as self-acceptance, kindness toward oneself, recognizing that suffering is part of the human experience, and mindfulness. The improvement of self-compassion is facilitated through self-reflection, religious activities, and community support. The findings suggest that strengthening self-compassion, particularly through an Islamic counseling approach, is crucial in supporting the mental health of housewives in rural areas. Additionally, the study highlights the importance of community-based empowerment programs to enhance the psychological resilience of housewives, particularly in fostering a supportive environment for their well-being.